"For the good of mankind": The legacy of nuclear testing in Micronesia - Seiji Yamada; Matthew Akiyama (Social Medicine Publication Group, 2013)
US government research on the health effects of exposure to radiation from nuclear weapons in-volved gross violations of the human rights of peo-ple in the Marshall Islands. In all likelihood, fallout from US nuclear weapons testing in the Pacific was deposited on other Micronesian islands. The US government should release the classified data it pos-sesses on the history of nuclear testing, fallout pat-terns, and the effects on the people of the Marshall Islands and the rest of Micronesia. Health workers should work to ensure that nuclear-armed states ful-fill their treaty obligations to pursue negotiations toward the elimination of nuclear weapons. As a matter of social justice, in order to ensure the human right to health, the federal government should ex-tend Medicaid eligibility to all Micronesian people from the Compact of Free Association nations.